2017
DOI: 10.7287/peerj.preprints.3086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preventive effects of salvia officinalis leaf extract on insulin resistance and inflammation, in high fat diet-induced-obesity mice model

Abstract: Background: Salvia officinalis (sage) is a native plant to the Mediterranean region and has been used for a long time in traditional medicine for various diseases. We investigated possible anti-diabetic, anti-inflammatory and anti-obesity effects of sage methanol (MetOH) extract in a nutritional mouse model of obesity, inflammation and insulin resistance, as well as its effects on lipolysis and lipogenesis in 3T3-L1 cells. Methods: Diet-induced obese (DIO) mice were treated for 5 weeks with sage me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…(2019) reported that the ME of Anatolian Salvia species including S. verbenaca inhibited effectively the α‐glucosidase enzyme with low concentrations. Various studies on different Salvia species were focused on the strong anti‐diabetic efficacies of different extracts compounds (Adımcılar et al., 2019; Bahadori et al., 2017; Ben Khedher et al., 2018; Eidi & Eidi, 2009; Mocan et al, 2018; Nickavar, Abolhasani, & Izadpanah, 2010). In a previous study, the methanol extract of Salvia acetabulosa showed the highest inhibitory activity compared to the chloroform or hexane extracts (Loizzo et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(2019) reported that the ME of Anatolian Salvia species including S. verbenaca inhibited effectively the α‐glucosidase enzyme with low concentrations. Various studies on different Salvia species were focused on the strong anti‐diabetic efficacies of different extracts compounds (Adımcılar et al., 2019; Bahadori et al., 2017; Ben Khedher et al., 2018; Eidi & Eidi, 2009; Mocan et al, 2018; Nickavar, Abolhasani, & Izadpanah, 2010). In a previous study, the methanol extract of Salvia acetabulosa showed the highest inhibitory activity compared to the chloroform or hexane extracts (Loizzo et al., 2008).…”
Section: Discussionmentioning
confidence: 99%